Systemic immune-inflammation index as a prognostic marker in patients with newly diagnosed metastatic nasopharyngeal carcinoma: a propensity score-matched study - Lin, Cheng; Lin, Sheng; Guo, Qiao-Juan; Zong, Jing-Feng; Lu, Tian-Zhu; Lin, Na; Lin, Shao-Jun; Pan, Jian-Ji (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Systemic immune-inflammation index (SII) is significantly associated with poor survival in variety of cancers. However, SII has not yet been investigated in patients with newly diagnosed metastatic nasopharyngeal carcinoma (mNPC). Thus, our aim is to explore the role of SII in metastatic Nasopharyngeal Carcinoma. Methods: Two hundred and forty-three patients with newly diagnosed mNPC were retrospectively enrolled. The Kaplan-Meier analysis and Cox regression analysis was performed to evaluate the prognostic value of SII in overall survival (OS) and progression-free survival (PFS). Heterogeneity of factors was balanced by using propensity score-matched (PSM) analysis (1:1 for high SII versus low SII). Results: Kaplan-Meier analysis showed that patients with high SII were associated with poor median OS (18.0 vs. 36.0 m, P